Stomata and Pollen Grains Studies of Cotton (Gossypium hirsutum L.) in Iraq - Fathulla, Chnar Najmaddin; Bahar Jalal Mahmood (Zanco Journal of Pure and Applied Sciences, 2024)
The Gossypium hirsutum genotypes were have been different types of stomata as anisocytic, paracytic, hemi-paracytic and tetracytic with presence in both surfaces, and found conjugated stomata. The stomata generally composed of two guard cells with ordinary epidermal cells, while some genotypes composed of one guard cell. The pollen grains were colporated, prolate, sub-prolate, and prolate-spheroidal in shaped with echinus orientation sculpture.